2021
DOI: 10.12982/vis.2021.034
|View full text |Cite
|
Sign up to set email alerts
|

Keys to good knowledge, attitude and practice on rabies prevention in disease-free communities

Abstract: Many developing countries have recently faced public health challenges due to outbreaks of human rabies, while some areas have remained free from outbreaks of the disease. The aim of this study was to identify keys to good knowledge, attitude and practice (KAP) in rabies-free areas of Thailand to provide a functional model for rabies prevention in endemic zones. A cross-sectional study was conducted using a questionnaire in conjunction with interviews that were designed to elicit relevant information. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…25 - 27 Reasons for inadequate knowledge range from little inculcation to young students' lower performance on knowledge tests. 27 , 28 The reason why youngers have lower rabies knowledge than older may have been that were adults able to recall personal experiences of witnessing rabies cases. 27 Additionally, there exist some knowledge gaps between age groups, particularly related to the typical clinical signs of rabies in animals, risk situations to infect rabies, and basic rabies laws, especially Rabies Act B.E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 - 27 Reasons for inadequate knowledge range from little inculcation to young students' lower performance on knowledge tests. 27 , 28 The reason why youngers have lower rabies knowledge than older may have been that were adults able to recall personal experiences of witnessing rabies cases. 27 Additionally, there exist some knowledge gaps between age groups, particularly related to the typical clinical signs of rabies in animals, risk situations to infect rabies, and basic rabies laws, especially Rabies Act B.E.…”
Section: Discussionmentioning
confidence: 99%
“…24 We found that 52.1% of the respondents had inadequate rabies knowledge, consistent with similar studies on rabies in Thailand. [25][26][27] Reasons for inadequate knowledge range from little inculcation to young students' lower performance on knowledge tests. 27,28 The reason why youngers have lower rabies knowledge than older may have been that were adults able to recall personal experiences of witnessing rabies cases.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 10 Many developing countries have recently faced public health challenges due to rabies, even though some areas have remained free from rabies. 11 Similarly, rabies disease has an economic burden, particularly in developing countries. 6 Therefore, rabies prevention and control, in general, must be adopted to restrict or eradicate virus transmission by immunizing selected reservoir populations.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of public preferences for communication, wired broadcasting was the most common mode of public communication that was effective in conveying rabies knowledge throughout communities in Thailand (Kiratitana-olan et al, 2021). As a result, community leaders or village chiefs were entrusted with sharing accurate information and announcing rabies activities through wired broadcasting.…”
Section: Discussionmentioning
confidence: 99%